RACE AND ETHNICITY Culture, identity and representation - Spencer, Steve (Routledge, Taylor & Francis Group, 2014)
Broad-ranging and comprehensive, this completely revised and updated textbook is a critical guide to issues and theories of 'race' and ethnicity. It shows how these concepts came into being during colonial domination and how they became central - and until recently, unquestioned - aspects of social identity and division. This book provides students with a detailed understanding of colonial and post-colonial constructions, changes and challenges to race as a source of social division and inequality. Drawing upon rich international case studies from Australia, Guyana, Canada, Malaysia, the Caribbean, Mexico, Ireland and the UK, the book clearly explains the different strands of theory which have been used to explain the dynamics of race. These are critically scrutinised, from biological-based ideas to those of critical race theory. This key text includes new material on changing multiculturalism, immigration and fears about terrorism, all of which are critically assessed. Incorporating summaries, chapter-by-chapter questions, illustrations, exercises and a glossary of terms, this student-friendly text also puts forward suggestions for further project work. Broad in scope, interactive and accessible, this book is a key resource for undergraduate students of 'race' and ethnicity across the social sciences.